Fibrosis and MAGNIFI-CD Activity Index at Magnetic Resonance Imaging to Predict Treatment Outcome in Perianal Fistulizing Crohn's Disease Patients. (2nd October 2021) - van Rijn, Kyra L; Meima-van Praag, Elise M; Bossuyt, Patrick M; D'Haens, Geert R; Gecse, Krisztina B; Horsthuis, Karin; Snijder, Harmanna J; Tielbeek, Jeroen A W; Buskens, Christianne J; Stoker, Jaap
Abstract: Background and Aims: Characteristic magnetic resonance imaging [MRI] features associated with long-term perianal fistula closure are still being discussed. This study evaluated the predictive value of degree of fibrosis and disease activity (MAGNIFI-CD index) at MRI for long-term clinical closure of Crohn's perianal fistulas. Methods: Crohn's disease [CD] patients treated with surgical closure following anti-tumour necrosis factor [anti-TNF] induction or anti-TNF alone for high perianal fistulas as part of a patient preference randomized controlled trial [PISA-II] between 2013 and 2020 with a post-treatment MRI and long-term clinical follow-up data were retrospectively included. Two radiologists scored the degree of fibrosis and MAGNIFI-CD index at pre- and post-treatment MRI. The accuracy of post-treatment MRI findings in predicting long-term clinical closure [12 months after the MRI] was evaluated using receiver operating characteristics [ROC] analysis. Results: Fifty patients were included: 31 female, median age 33 years (interquartile range [IQR] 26–45). Fourteen patients showed a 100% fibrotic fistula at post-treatment MRI, all of which had long-term clinical closure. Median MAGNIFI-CD index at post-treatment MRI was 0 [IQR 0–5] in 25 patients with long-term clinical closure and 16 [IQR 10-20] in 25 patients without. ROC analysis showed an area under the curve of 0.90 (95% confidence interval [CI] 0.82–0.99) for degree of fibrosis and 0.95 [95% CI 0.89–1.00] for the MAGNIFI-CD index, with a Youden cut-off point of 6 [91% specificity, 87% sensitivity]. Conclusions: Degree of fibrosis and MAGNIFI-CD index at post-treatment MRI are accurate in predicting long-term clinical closure and seem valuable in follow-up of perianal CD. A completely fibrotic tract at MRI is a robust indicator for long-term fistula closure. EudraCT: 2013-002932-25 and 2018-002064-15 Graphical Abstract: